2018
DOI: 10.1021/acs.biochem.8b00302
|View full text |Cite
|
Sign up to set email alerts
|

Fern-9(11)-ene-2α,3β-diol Action on Insulin Secretion under Hyperglycemic Conditions

Abstract: The objective of this study was to investigate the effect and the mechanism of action of fernenediol as an insulin secretagogue. Wistar rats were treated with 0.1, 1, and 10 mg/kg fernenediol before inducing hyperglycemia by oral glucose. The glycaemia, insulin, LDH, calcium, and hepatic glycogen were analyzed. Considering the intestine and pancreas as targets for the triterpene action, the duodenum was used to verify the influence of fernenediol on intestinal glycosidases. Additionally, pancreatic islets were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
1
1
0
Order By: Relevance
“…Our study demonstrated that the inhibitor PKI-(6-22)-amide prevented the migration of uvaol-provoked fibroblast and endothelial cells; thus, this PKA signaling pathway is likely involved in uvaol-induced migration. These findings support previous studies, which showed that other triterpenoids, such as ursolic acid [39], astragaloside [40], and fernenediol [41], induce the activation of the PKA pathway to generate their pharmacological effects. Of note, the activation of PKA intracellular signaling pathways upregulates ECM production by fibroblasts, contributing to tube formation and the motility of endothelial cells [42,43].…”
Section: Discussionsupporting
confidence: 92%
“…Our study demonstrated that the inhibitor PKI-(6-22)-amide prevented the migration of uvaol-provoked fibroblast and endothelial cells; thus, this PKA signaling pathway is likely involved in uvaol-induced migration. These findings support previous studies, which showed that other triterpenoids, such as ursolic acid [39], astragaloside [40], and fernenediol [41], induce the activation of the PKA pathway to generate their pharmacological effects. Of note, the activation of PKA intracellular signaling pathways upregulates ECM production by fibroblasts, contributing to tube formation and the motility of endothelial cells [42,43].…”
Section: Discussionsupporting
confidence: 92%
“…Insulin levels were estimated by means of colorimetric measurements at 450 and 550 nm through interpolation from a standard curve. Samples were analysed in duplicate and results were expressed as ng insulin/ml serum (Castro et al, 2018). The sensitivity of the assay was 5 µUI/mL.…”
Section: Insulin Serum Measurementmentioning
confidence: 99%